#TITLE_ALTERNATIVE# - Puput Erlangga (NIM 102 03 065), Mokhammad
Abstract : Rock physics of Sidoarjos mud characterization is an absolute pre-requirement for understanding the rock physics nature of mud, minerals contain and the position of the mud source in subsurface. Rock physics natures in examples are elasticity, viscosity, and resistivity. To identify the mineral contain of the mud, we should used X-Ray diffraction, Scanning Electron Microscope, Viscosity meter, and Seiscore High Pressure High Temperature Set Equipment. According to the elasticity of mud, especially Poissons Ratio, we can estimate precisely the position of the mud source by combining among the poissons ratio measurement methods : poissons ratio of the samples, computed poissons ratio of log data, and poissons ratio section from AVO inversion, we can predict the original of mud source position in the subsurface quantitatively.